ACE2 and SARS-CoV-2 Infection Risk: Insights From Patients With Two Rare Genetic Tubulopathies, Gitelman's and Bartter's Syndromes - Calò, Lorenzo A.; Rigato, Matteo; Sgarabotto, Luca; Gianesello, Lisa; Bertoldi, Giovanni; Ravarotto, Verdiana; Davis, Paul A. (Frontiers in Medicine, 2021)
COVID-19 is spreading globally with Angiotensin Converting Enzyme (ACE)-2 serving as the entry point of SARS-CoV-2 virus. This raised concerns how ACE2 and Renin-Angiotensin (Ang)-System (RAS) are to be dealt with given their roles in hypertension and their involvement in COVID-19’s morbidity and mortality. Specifically, increased ACE2 expression in response to treatment with ACE inhibitors (ACEi) and Ang II receptor blockers (ARBs) might theoretically increase COVID-19 risk by increasing SARS-CoV-2 binding sites. However, ACE2 is part of the protective counter‐regulatory ACE2‐Ang1‐7‐MasR axis, which opposes the classical ACE-AngII-AT1R regulatory axis. We used Gitelman’s and Bartter’s syndromes (GS/BS) patients, rare genetic tubulopathies, who that have endogenously increased levels of ACE2, to provide more clarity/insight onexplore these issues. Specifically, 128 genetically confirmed GS/BS patients, living in Lombardia, Emilia Romagna and Veneto, the Northern Italy hot spots for COVID-19, were surveyed via telephone survey regarding COVID-19. The survey found no COVID-19 infection and absence of COVID-19 symptoms in any patient. Comparison analysis with the prevalence of COVID-19 in those Regions showed statistical significance (p<0.01). The results of the study strongly suggest that , contribute to suggest that increased ACE2 does not increase risk of COVID-19 and that ACEi and ARBs by blocking excessive AT1R-mediated Ang II activation, might favor the increase of ACE2-derived Ang 1-7.